2019
DOI: 10.1002/jbm4.10127
|View full text |Cite
|
Sign up to set email alerts
|

PDGF Modulates BMP2‐Induced Osteogenesis in Periosteal Progenitor Cells

Abstract: BMPs are used in various clinical applications to promote bone formation. The limited success of the BMPs in clinical settings and supraphysiological doses required for their effects prompted us to evaluate the influence of other signaling molecules, specifically platelet‐derived growth factor (PDGF) on BMP2‐induced osteogenesis. Periosteal cells make a major contribution to fracture healing. We detected broad expression of PDGF receptor beta (PDGFRβ) within the intact periosteum and healing callus during frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 42 publications
(96 reference statements)
0
51
0
Order By: Relevance
“…Mouse periosteal cells were isolated from either WT or Osterix-conditional YAP/TAZ deficient (YAP cKOi ;TAZ cKOi ) femurs on 4 dpf and cultured at 37°C and 5% O2, as described previously (29) . Briefly, mice were anesthetized by carbon dioxide inhalation and euthanized via cervical dislocation.…”
Section: Periosteal Cell Isolation and Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse periosteal cells were isolated from either WT or Osterix-conditional YAP/TAZ deficient (YAP cKOi ;TAZ cKOi ) femurs on 4 dpf and cultured at 37°C and 5% O2, as described previously (29) . Briefly, mice were anesthetized by carbon dioxide inhalation and euthanized via cervical dislocation.…”
Section: Periosteal Cell Isolation and Osteogenic Differentiationmentioning
confidence: 99%
“…To elucidate if inducible YAP/TAZ deletion regulated periosteal osteoprogenitor differentiation, we isolated activated periosteal progenitor cells at 4 dpf ( Fig. 7G) (28,29) . Following culture for 21 days in osteogenic media, inducible, Osterix-conditional YAP/TAZ deletion reduced mineral deposition stained with Alizarin Red (Fig.…”
Section: Inducible Osterix-conditional Yap/taz Deletion Reduced Periomentioning
confidence: 99%
“…Interestingly, of the major growth factor receptors involved in fracture healing, PI3K can only directly bind PDGF-receptors (PDGFRs). Additionally, it has been recently published that a majority of murine periosteal cells post-fracture express the homodimer PDGFRβ or the heterodimer PDGFRα/β, while few express PDGFRα alone [20]. While a direct interaction between PI3K and PDGFRs is critical for skeletal development [2123], this requirement in the context of periosteal response to fracture healing has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…We used two murine strains of MSCs in the current study to investigate the co-expression GM MSCs. It is been reported that PDGF-BB enhanced the proliferation of several cell types including endothelial cells [6] and populations of MSCs [31,32]. By studying the cell proliferation and cell viability, the results showed that the presence of PDGF-BB from GM MSCs or exogenous PDGF-BB protein in BALB/c MSCs increased cell proliferation and cell viability.…”
Section: Discussionmentioning
confidence: 91%
“…Recombinant human PDGF-BB (rhPDGF-BB) in combination with an osteoinductive tricalcium phosphate (TCP)-collagen matrix has been applied clinically in ankle and hindfoot arthrodesis, and was shown to be a safe and effective alternative to autograft [33,34]. In vitro and in vivo studies have previously demonstrated the capacity for PDGF-BB to facilitate osteogenesis by stem cells [7,31,32]. Furthermore, PDGF-BB secreted by preosteoclasts induced angiogenesis during coupling with osteogenesis [6].…”
Section: Discussionmentioning
confidence: 99%